OZCEL (OZ CARE AND CLEAN) PENGEMBANGAN ALAT PEMBASMI HAMA MENGGUNAKAN OZONISASI SEBAGAI UPAYA PENGGANTI PESTISIDA PADA PERTANIAN - Suhiyar, Awal Bahtera; Pamulang, Ligan Ayu; Prayogo, Ari (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
Abstract The research objectives are to (1) design Ozcel(Oz Care and Clean) using ozonization (2) to find out how it works and (3) to reveal its performance as an effort to substitute pesticides. The type of the research is a development research. The process of making Ozcel covers designing, preparing the equipment and materials, making the electronic circuit of PWM driver, making a box and lay out, assembling the parts of Ozcel, and testing the function of Ozcel as a pest eradicator. The result of the research is the design of Ozcel (Oz Care and Clean) consisting of important components, which among other things are a motorcycle coil as a high voltage generator functioning as ozone gas generator and PWM circuit as the driver of the coil. The dimension of Ozcel is 25 x 15 x 15 cm. Ozcel works as the high voltage of the coil is generated to produce electric plasma. The oxygen is then flown through the plasma and the oxygen will react to become ozone or O3. Based on the analysis of its performance, Ozcel (Oz care and clean), is shown to have an effcet on preserving fruits after the harvest. Ozcel makes the fruits and vegetables remain fresh longer. In this way the preserving process is carried out without using preservatives and is environment friendly.